STRONGER: CROWDSOURCING STRATEGIES IN OPTIMIZING VOLUNTEER LOGISTICSTIMES OF DISASTER AND SUPPLY CHAIN - Nurali Nurali; Emmelia Kristina Hutagaol; Rina Sunartyas Ramdhani; Agus Paryadi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Indonesia faces one of the highest disaster risks in the world, including floods, landslides, and volcanic eruptions. The main challenges in disaster management are delays in aid distribution, overlapping logistics, and a lack of coordination between stakeholders. This study aims to design a crowdsourcing strategy that optimizes the role of MSMEs and local communities in the volunteer logistics system during disasters through the STRONGER model (Collaborative Strategy of MSMEs and Local Communities in Optimizing Volunteer Logistics). The study used a qualitative case study approach in Bogor Regency, using in-depth interviews, observation, and document analysis. A total of 50 respondents were involved, consisting of MSMEs, volunteers, and local government officials. The results show that MSME involvement improves the efficiency of providing basic needs, while local communities act as distribution bridges and report on real needs in the field. A simple digital platform supports real-time needs mapping, although digital literacy challenges remain. The STRONGER model has proven relevant in accelerating aid distribution, strengthening cross-actor collaboration, and encouraging local economic recovery. This study recommends integrating STRONGER into regional disaster logistics policies and has important implications for sustainable development based on local potential.